THE EFFECT OF CURRENT RATIO AND DEBT TO ASSET RATIO ON STOCK RETURN WITH EARNINGS PER SHARE AS A MODERATING VARIABLE - Thezar Fiqih Hidayat Hasibuan (CV. Radja Publika, 2025)
This study aims to test the effect of Current Ratio (CR), and Debt to Asset Ratio (DAR) on Stock Returns using Earning Per Share as a moderating variable. The objects of this study were 21 mining companies listed on the Indonesia Stock Exchange from 2018-2021. The sample was selected using the purposive sampling method, namely 121 companies. The analysis method used in this study is multiple linear regression analysis with moderating variables. The results of this study indicate that variables X1 and X2 are able to influence Stock Returns, and the Moderation variable is able to strengthen the influence of the independent variable on the dependent variable.